The ethics of aesthetics in Kawabata Yasunari. - Siti Rohana Binte Mohamed Akhbar. (2013)
Kawabata YasunariI, novelist and master ofthe short story and Japan's first Nobel Prize laureate for literature, by his own self-professed aims, made beauty his life business. "All my life," he proclaims, "is a search of beauty, and I will continue searching for it to the moment ofmy death." That his writing is beautiful is treated rather as a given. It is the one point of convergence in opinion of Kawabata's disparate commentators, who all agree that the distinction ofKawabata's literature is to palpably reorder reality into art. His aesthetics, however, is as celebrated as it is problematic; largely because of his Nobel Prize acceptance speech and its glorification of 'Japaneseness' with overtones that have been described as culturally racist, imperialist or even fascist. So strong are these overtones that his literature, especially the novels this essay focuses on - Snow Country, Thousand Cranes and House ofthe Sleeping Beauties - has inevitably been framed within its context. The discussions that follow build upon the argument that in the protagonists' self-effacing surrender to a purely aestheticised ideal, their author comes too uncomfortably close to the language of fascism. That the lyrical beauty ofKawabata's poetry prose has been described as reminiscent of haiku in its episodic brevity and reliance on the device of "internal comparison" (Akmakjian 14), No in its "structure of discovery, when the reader or spectator begins on the outside and works his or her way towards the central concern" (Rimer, Modern 9) and sumi-e, where that which is explicitly depicted is only the foreground; a mere distillation of what lies beyond in